A spring of living waters in a pool of metaphors: The metaphorical landscape of 1QHa 16:5–27 - Dhont, Marieke (HTS teologiese studies, 2021)
This research article focuses on the use of the water metaphor in column 16 of the Hodayot. Previous scholarship has often concentrated on the garden metaphor in this section, particularly on its intertextual links with the book of Isaiah. By drawing on contemporary metaphor theory, in particular blending theory, I show how the author of the Hodayot creates poetry through a multiple blended network of garden and water metaphors, and how aspects of the linguistic form of the poem, in particular the phrase מבוע מים חיים‘well of living waters’, can be read as an expression of this blend. The aim of this study is to contribute (1) to the study of the Hodayot and its poetic practices, against older dismissals of the poetic quality of the Hodayot, and (2) to our understanding of semantic constellations and the conceptual world of ancient Judaism.Contribution: This article fits within the scope of HTS’s theme ‘Historical Thought and Source Interpretation’ as it contributes to our insights into ancient Jewish thought through the interpretation of a religious source text using metaphor theory.